Effects of third party errors - Andrej E. Sastitko (Russian Presidential Academy of National Economy and Public Administration (RANEPA), 2013)
Type-I and type-II errors effects do matter both from the rules enforcement perspective and vertically upward to rules enactment. The paper support conventional idea about detrimental influence on deterrence of both types of errors. At the same time special role of type-I errors is demonstrated based on strategic interaction between economic exchange participants supported by third-party enforcement with opportunities to discriminate players. The paper highlights the issue that errors in enforcement is not whole story: the simple classification of cases is suggested from the perspective of type-I and type-II errors in rules enforcement and rules enactment.
Keywords: D02; K10; K42; P48; 330; types-I&II errors; institutions; rules enforcement; rules enactment; discrimination; Nash equilibrium